Helminthological records of six-banded Armadillos Euphractus sexcinctus (Linnaeus, 1758) from the Brazilian semi-arid region, Patos county, Paraiba state, including new morphological data on Trichohelix tuberculata (Parona and Stossich, 1901) Ortlepp, 1922 and proposal of Hadrostrongylus ransomi nov comb. - Hoppe, E. G. L. [UNESP]; Araujo de Lima, R. C. [UNESP]; Tebaldi, J. H. [UNESP]; Athayde, A. C. R.; Nascimento, Adjair Antônio do [UNESP] (Int Inst Ecology, 2009)
This work aimed to evaluate the gastrointestinal helminthfauna composition of six-banded armadillos from the Brazilian semi-arid region. Gastrointestinal contents of six road-killed adult animals from Patos County, Paraiba State, were analyzed. Six species of nematodes, comprising five genera and four families, were recovered from the analyzed animals. New morphological data on Trichohelix tuberculata is given, along with a new taxonomical proposal for Hadrostrongylus ransomi (Travassos, 1935) n. comb. This is the first record for parasitic helminths in this host from the Brazilian semi-arid.
Keywords: Caatinga biome; Euphractus sexcinctus; Nematoda; Trichohelix tuberculata; Hadrostrongylus ransomi